Re-description of the tadpole of Pseudopaludicola falcipes (Anura: Leiuperidae), with comments on larval diversity of the genus - Laufer, Gabriel; Barreneche, Juan M. (Zootaxa, 2008)
The genus Pseudopaludicola consists of 12 Neotropical species, whose biology is not well known. Only four larvae of this genus have been described. The first one to be described was P. falcipes, but available reports are incomplete and the morphology description is inconsistent, especially in oral disc configuration. P. falcipes was posteriorly re-described based only on adult specimens, and its geographic distribution was restricted. Therefore, there is a need to examine tadpole morphology of this genus in order to provide a new larval description. In this paper we re-describe the tadpole of P. falcipes and compare it with other species of the genus Pseudopaludicola. Our description is based on specimens collected at three different localities in northern Uruguay, with series reared in the laboratory. We report a novel oral disc configuration: the uniserial marginal papillae present a wide upper gap and a narrow lower gap followed by two lateral gaps. We also analyze the previously ignored oral disc diversity among Leiuperidae larvae, which must be taken into account in comparisons between species for systematic purposes and ecological studies. Morphometric comparisons with P. boliviana tadpole reveal that P. falcipes is larger, having a narrower and shorter snout, and a greater narial-ocular distance. P. falcipes larvae belong to the lentic bentonic ecomorphological guild.